2016
DOI: 10.1016/j.jvs.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Management of concomitant abdominal aortic aneurysm and colorectal cancer

Abstract: Among different approaches, no significant differences in 30-day outcomes among patients treated in either two or one stage were evident. EVAR showed the lowest mortality and also diminished the delay between the two procedures in <2 weeks for a two-stage approach, although it has been associated with a significant risk for thrombotic events. The coexistence of AAA and CRC seems to favor the use of EVAR in treating those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Both OSR and EVAR of the intact AAA did not increase mortality in patients with a history of cancer. In contrast, previous study by Kouvelos et al of AAA repair in patients with synchronous malignancy showed higher mortality and morbidity [3]. Since we looked at a history of cancer rather than synchronous cancer, there could have been a longer time interval between the cancer treatment and AAA repair.…”
Section: Short-term Mortalitymentioning
confidence: 64%
See 1 more Smart Citation
“…Both OSR and EVAR of the intact AAA did not increase mortality in patients with a history of cancer. In contrast, previous study by Kouvelos et al of AAA repair in patients with synchronous malignancy showed higher mortality and morbidity [3]. Since we looked at a history of cancer rather than synchronous cancer, there could have been a longer time interval between the cancer treatment and AAA repair.…”
Section: Short-term Mortalitymentioning
confidence: 64%
“…Many studies have analyzed the effect of AAA repair in patients with synchronous malignancy and showed increased short-term mortality and morbidity after both endovascular aortic repair (EVAR) and open surgical repair (OSR) [3]. In addition, patients with intra-abdominal tumors have increased perioperative mortality after OSR of AAA, and the history of intra-abdominal procedures may hinder OSR due to the development of adhesions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported advantages of EVAR over open repair in managing concomitant cancer and AAA. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…As the aging population increases, the incidence of gastrointestinal cancer and vascular diseases, such as abdominal aortic aneurysm (AAA) and abdominal aortic dissection (AAD), has increased [1, 2]. Though the true incidence is difficult to accurately ascertain, the synchronous presentation of AAA or AAD and gastrointestinal tumor is still rare (0.49% to 2.1% in most series [3, 4]). In the absence of a clear consensus from the literatures, the management of this clinical presentation remains perplexing and controversial, especially in establishing the optimal treatment approach and the benefit of the patients [1, 3].…”
Section: Introductionmentioning
confidence: 99%